Haploidentical transplant in patients with myelodysplastic syndrome - Robin, Marie; Radujković, Aleksandar (Blood advances, 2017)
Nonrelapse mortality remains high in MDS patients who underwent haploidentical transplant before 2015. Haplotransplantation using PT-CY and reduced-intensity conditioning seems an acceptable option in MDS patients lacking HLA-matched donors. The only curative treatment in patients with intermediate or high-risk myelodysplastic syndrome (MDS) is allogeneic hematopoietic stem cell transplantation (HSCT), which usually results in a long-term, disease-free survival rate of between 30% and 50%, depending on the disease risk and the type of donor. In patients without an HLA-matched sibling donor, a family haploidentical donor is an alternative option. The present study reports the European Group for Blood and Marrow Transplantation activity for haploidentical transplantation in MDS patients. A total of 228 patients transplanted from a mismatched HLA-related donor between 2007 and 2014 were studied. The median age at transplant was 56 years. Eighty-four (37%) patients had MDS transformed into acute myeloid leukemia at the time of transplant. Ex vivo T-cell depletion was used in 34 patients. One hundred ninety-four patients received a T-cell replete transplant and 102 patients received posttransplant cyclophosphamide (PT-CY) as graft-versus-host disease (GVHD) prophylaxis. The cumulative incidences of acute and chronic GVHD in PT-CY vs other patients were 25% vs 37% and 37% vs 24%, respectively. The cumulative incidence of nonrelapse mortality was 55% in patients who did not receive PT-CY (no PT-CY) and 41% in patients who did receive PT-CY. Three-year overall survival was 28% in no PT-CY patients and 38% in PT-CY patients. In multivariable analysis, the main risk factors were the intensity of the conditioning regimen and the use of PT-CY. In conclusion, the outcomes of MDS patients who received an haploidentical transplant are close to the results other transplantations from HLA-mismatched donors with approximately one-third of patients alive and free of disease 3 years after transplant, and the use of PT-CY may improve their outcomes.,